Risk factors for progressive axonal degeneration of the retinal nerve fibre layer in multiple sclerosis patients - Garcia-Martin, Elena; Pueyo, Victoria; Almarcegui, Carmen; Martin, Jesus; Ara, Jose R; Sancho, Eva; Pablo, Luis E; Dolz, Isabel; Fernandez, Javier (British journal of ophthalmology, 2011)
AimTo quantify structural and functional degeneration in the retinal nerve fibre layer (RNFL) of patients with multiple sclerosis (MS) over a 2-year time period, and to analyse the effect of prior optic neuritis (ON) as well as the duration and incidence of MS relapses.Methods166 MS patients and 120 healthy controls underwent assessment of visual acuity and colour vision, visual field examination, optical coherence tomography, scanning laser polarimetry and visual evoked potentials (VEPs). All subjects were re-evaluated after a period of 12 and 24 months.ResultsChanges in the optic nerve were detected by structural measurements but not by functional assessments. Changes registered in MS patients were greater than changes in healthy controls (p<0.05). Eyes with previous ON showed a greater reduction of parameters in the baseline evaluation, but RNFL atrophy was not significantly greater in the longitudinal study. Patients with MS relapses showed a greater reduction of RNFL thickness and VEP amplitude compared with non-relapsing cases. Patients with and without treatment showed similar measurement reduction, but the non-treated group had a significantly higher increase in Expanded Disability Status Scale (p=0.029).ConclusionsMS causes progressive axonal loss in the optic nerve, regardless of a history of ON. This ganglion cell atrophy occurs in all eyes but is more marked in MS eyes than in healthy eyes.